ANALISIS KEMAMPUAN KONEKSI MATEMATIS DAN MOTIVASI BELAJAR SISWA SMK - Imas Muslihat; Dian Andriani; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze students' mathematical connection ability in solving the system problems of linear variables two variables and learning motivation of students of class X-OTKP 1 Computer Vocational School AKP Cianjur. The subject of this study of 21 students. The method used in this research is descriptive qualitative. Data collection techniques are done by giving a test of mathematical connection ability and learning motivation questionnaire, then, data is processed and analyzed through three stages, namely checking the results of student answers, presenting student test data and questionnaires, and drawing conclusions from the results of the study. The results of the data show that the mathematical connection ability in the indicator recognizes representation is equivalent to the same concept, obtained data of students who answer correctly that is equal to 33.33% and students who answer incorrectly are 66.67%. For indicators using and assessing the relevance of topics between mathematics, data obtained from students who answered correctly were 38.10% and students who answered incorrectly were 61.90%. For indicators using mathematics in everyday life, data obtained by students who answered correctly was equal to 47.62% and students who answered incorrectly were 52.38%. So it can be concluded that students' mathematical connection ability is classified as low. However, students have high learning motivation in mathematics learning which is equal to 80.71%.